2014
DOI: 10.1186/bcr3613
|View full text |Cite|
|
Sign up to set email alerts
|

Timing of pubertal stages and breast cancer risk: the Breakthrough Generations Study

Abstract: IntroductionBreast development and hormonal changes at puberty might affect breast cancer risk, but epidemiological analyses have focussed largely on age at menarche and not at other pubertal stages.MethodsWe investigated associations between the timing of pubertal stages and breast cancer risk using data from a cohort study of 104,931 women (Breakthrough Generations Study, UK, 2003–2013). Pubertal variables were reported retrospectively at baseline. Breast cancer risk was analysed using Cox regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
114
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 30 publications
11
114
2
Order By: Relevance
“…We adopted a conservative statistical approach to provide robust confirmation that early menarche in women is associated with higher risks for T2D and cardiovascular disease. We also confirmed the linear associations between increasing age at menarche and higher risks for osteoporosis17 but lower risks for breast cancer6, which are both likely consequences of altered duration of exposure to reproductive levels of sex hormones. Furthermore, our findings substantially expand the range of associated adverse health outcomes, highlighting many with little or no prior link to age at menarche.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We adopted a conservative statistical approach to provide robust confirmation that early menarche in women is associated with higher risks for T2D and cardiovascular disease. We also confirmed the linear associations between increasing age at menarche and higher risks for osteoporosis17 but lower risks for breast cancer6, which are both likely consequences of altered duration of exposure to reproductive levels of sex hormones. Furthermore, our findings substantially expand the range of associated adverse health outcomes, highlighting many with little or no prior link to age at menarche.…”
Section: Discussionsupporting
confidence: 79%
“…It is reasonably well-recalled into adulthood and has therefore been included in many epidemiological studies3, with growing evidence that early age at menarche is associated with higher risks for subsequent obesity, type 2 diabetes (T2D)4 and cardiovascular disease5. Other reported associations with early menarche include higher risks for breast cancer6 and all-cause mortality7 and there are less consistent links described with depression and low bone mineral density89. In men, the evidence for such associations is sparse due to the lack of a convenient measure of puberty timing.…”
mentioning
confidence: 99%
“…22 Importantly, the study confirmed that the number of years between onset of breast development and menarche, referred to as tempo, may affect risk over and above the age at attainment of any single pubertal milestone. 22 Thus, the window between onset of breast development and first menses has become wider in most populations worldwide, 23,24 suggesting a possible future increase in breast cancer incidence. 21,25 Pubertal onset, defined as the beginning of breast and/or pubic hair development, is often assessed by using Tanner staging, 26 which is routinely used in clinical evaluations.…”
supporting
confidence: 53%
“…Puberty is a reproductive milestone that signals the onset of maturity, and early puberty is likely a risk for metabolic disease and breast cancer (Biro and Wolff, 2011; Bodicoat et al , 2014). Action of environmental agents during puberty may be an indirect pathway to later disease.…”
Section: Introductionmentioning
confidence: 99%